Annual Report on Exchange Arrangements and Exchange Restrictions 1967. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1967)
This paper discusses relaxation of restrictions in most cases that applied to trade; in some countries there was also liberalization with respect to invisibles. Yugoslavia introduced a major revision of its trade and payments system at the beginning of 1967 and has initiated steps to reduce its reliance on bilateral trade and payments arrangements; this took on greater significance because economic decision making within Yugoslavia has been decentralized further and made more responsive to market forces. India, by measures associated with devaluation, carried out a major simplification of export promotion measures and a substantial relaxation of restrictions on imports. Restrictions on imports were relaxed in other countries, including Austria, Iceland, Israel, Japan, Korea, Morocco, Rwanda, South Africa, and Uruguay. Progress in working off commercial and financial arrears occurred in several countries; particularly noteworthy were the starts made by Ghana and Indonesia. Colombia and Pakistan, each having progressively liberalized through most of the year, re-imposed import restrictions near the end of the year; Colombia, however, introduced new regulations in March 1967, which would permit a measure of liberalization of imports.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet